Yemen : Teachers - World Bank (Washington, DC, 2014)
Yemen is a low-income country with a young and growing secondary education population; female students exhibit lower enrollment rates, and the teaching force is largely male, especially in leadership positions. In 2008, Yemen spent 5.2 percent of Gross Domestic Product (GDP) on public education. In the early years of the decade (2001), Yemen was devoting 9.6 percent of GDP for public education provision. In 2008, Yemen spent 16 percent of total government expenditure on education. Yemen's education system consists of basic education from grades 1 to 9 (ages 6-14/15) and secondary education from grades 10 to 12 (ages 14/15-18). Over the past 5 years, noteworthy reforms in basic education have included the abolition of school fees, improvements in annual work planning, contracting of female teachers in remote parts of the country, tying of teacher posts to the school rather than to the individual, reductions in teacher absenteeism, and capacity-building at all levels of education service delivery. The majority of teachers is in the 30-to 39-year-old age bracket and is male, and leadership positions are primarily filled by men. The Ministry of Education (MoE) sets policies, and implementation is carried out by the sub-national (Governorate) and local (District) levels together with as local councils (Municipalities). All teachers can join the two national teacher organizations. Collective bargaining and strike action are legal, but permission must first be sought to render a strike legal. Teachers are offered few financial incentives or other opportunities for public recognition to reward strong performance. Performance-related pay and monetary bonuses for strong performance by individual teachers or by schools are not available.